Extreme snow metamorphism in the Allan Hills, Antarctica, as an analogue for glacial conditions with implications for stable isotope composition. Issue 230 (2015) - Dadic, Ruzica; Schneebeli, Martin; Bertler, Nancy A.N.; Schwikowski, Margit; Matzl, Margret
Abstract: Understanding physical processes in near-zero accumulation areas can help us to better understand polar ice-core records, particularly during periods when accumulation rates were lower than today. We report measurements from a 5 m firn core from the Allan Hills, Antarctica, which include physical properties using computer tomography, stable isotope ratios δD and δ 18 O, and 210 Pb activity. The core shows a highly metamorphosed firn with homogeneous and stable structure, but with discrete layers near the surface. The observed firn structure is caused by a combination of unique depositional and post-depositional processes. The irregular δD and δ 18 O signal does not follow the stratigraphic sequence and implies post-depositional modification caused by microscopic pressure gradients in the firn that can result from either forced ventilation over rough surfaces in the presence of wind or alternating temperature-gradients between the firn and the atmosphere. Our results also indicate impact snow deposition under high winds and with a high initial density and air exchange between the atmosphere and the snowpack. 210 Pb activity below 0.3 m falls below the detection limit, implying that most of the core is more than 100 years old. We conclude that the Allan Hills record provides a unique opportunity to investigate important processes that would have affected ice-core records from glacial periods.